AN APPLICATION OF VALUE ENGINEERING TO INCREASE VALUE OF SME'S PRODUCT (A STUDY ON SME PRODUCES SCHOOL HAT) - Ari Basuki (Universitas Trunojoyo Madura, 2018)
Value engineering is an approach that can be used to increase value of a product. This study employed value engineering approach to improve value of school's hat that is produced by small companies located in the Sidoarjo area. Through the application of value engineering, there are four alternatives considered as new idea generation by analyzing and substituting raw materials. Value of the existing product is 1,000 and it costs Rp.11.830,-. After made some analysis of new product alternatives and assessing the score of each options, the result is that alternative 1 has the highest value by 1,396. It means that alternative 1 serves as the best alternative with the smallest production cost as well (Rp.7.930).